2004
DOI: 10.1002/zaac.200400014
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assembling of Complex Tellurium Salts: Synthesis and Crystal Structures of {Cs[PhTeCl4]·CH3OH} and Cs[PhTeBr4]

Abstract: The direct reaction between PhTeCl3 and CsCl in methanol affords {Cs[PhTeCl4]·CH3OH}. Cs[PhTeBr4] was prepared by refluxing [2‐Br‐C5NH5][PhTeBr4] and CsCl in ethanol in the presence of an excess of HBr. In {Cs[PhTeCl4]·CH3OH} the [PhTeCl4]— units form dimers by secondary Te···Cl bonds with methanol molecules bridging adjacent Cs+ cations. In both compounds, the alkali metal cation interacts secondarily with the chlorine and bromine Te‐ligands, achieving singular coordination polyhedrons and holding the lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Recently, as part of our research on the coordination of organotellurium compounds, we have reported the syntheses and the molecular structures of organotellurium trihalides13,14 and organotellurium monohalides,11,15,16 as well as several studies involving structures of phenyltellurate halides stabilized by different cations 1719. Most of the crystal structures reported for the RTeX 3 species show that the occurrence of intra‐ and intermolecular interactions (secondary bonding), together with the nature of the organic groups bonded to the tellurium atoms, exert influence on the geometry around the tellurium( IV ) center and consequently define the structural patterns of these compounds 14,2026.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as part of our research on the coordination of organotellurium compounds, we have reported the syntheses and the molecular structures of organotellurium trihalides13,14 and organotellurium monohalides,11,15,16 as well as several studies involving structures of phenyltellurate halides stabilized by different cations 1719. Most of the crystal structures reported for the RTeX 3 species show that the occurrence of intra‐ and intermolecular interactions (secondary bonding), together with the nature of the organic groups bonded to the tellurium atoms, exert influence on the geometry around the tellurium( IV ) center and consequently define the structural patterns of these compounds 14,2026.…”
Section: Introductionmentioning
confidence: 99%
“…are well known [5][6][7][8]. Most of these complex salts lie close to the ionic/covalent borderline and show properties of supramolecules due to interionic, fairly strong secondary bonds of the types N + -HÁÁÁTe, TeÁÁÁX or XÁÁÁX (X = Cl, Br, I), as well as TeÁÁÁp-aryl contacts [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…C, 77 Se and 125 Te NMR measures were conducted in solutions of acetone-d6 and DMSO-d 6 in a 9:1 proportion, respectively. Since compounds 1 and 2 do not show many significant features in their1 H or 13 C NMR spectra, our attention was turned to the 77 Se and 125 Te NMR spectroscopy.…”
mentioning
confidence: 99%